2007
DOI: 10.1111/j.1467-7687.2007.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

What did Simon say? Revisiting the bilingual advantage

Abstract: Bilingual children often outperform monolingual children in tasks of cognitive control. This advantage may be a consequence of the fact that bilinguals have more practice controlling attention due to an ongoing need to manage two languages. However, existing evidence is limited because possible differences in ethnicity and socioeconomic status have not been properly controlled. To address this issue, we administered the Simon task to bilingual and monolingual children of identical ethnic and socioeconomic back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
349
5
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(379 citation statements)
references
References 45 publications
(101 reference statements)
17
349
5
8
Order By: Relevance
“…The role of SES in producing a bilingual advantage has been studied in relation to EF performance and is complicated by language status and the degree to which bilingual language proficiency is balanced (Carlson & Meltzoff, 2008;Pearson, 2007). Most relevant to the present research are data from Canadian 6-and 7-year-old bilinguals with a similar level of vocabulary in English and French that indicate the bilingual advantage on at least some EF tasks does not emerge when the SES of the bilingual and monolingual groups is controlled (Morton & Harper, 2007). In our investigation, there were no EF differences on either the DN or CS tasks between the monolingual Slovenian and bilingual children.…”
Section: Childhood Bilingualism and Conversation 15mentioning
confidence: 79%
“…The role of SES in producing a bilingual advantage has been studied in relation to EF performance and is complicated by language status and the degree to which bilingual language proficiency is balanced (Carlson & Meltzoff, 2008;Pearson, 2007). Most relevant to the present research are data from Canadian 6-and 7-year-old bilinguals with a similar level of vocabulary in English and French that indicate the bilingual advantage on at least some EF tasks does not emerge when the SES of the bilingual and monolingual groups is controlled (Morton & Harper, 2007). In our investigation, there were no EF differences on either the DN or CS tasks between the monolingual Slovenian and bilingual children.…”
Section: Childhood Bilingualism and Conversation 15mentioning
confidence: 79%
“…This advantage, which is supported by many studies (Bialystok, 1999;Costa et al, 2008), has been communicated to the general public through significant media coverage (Bhattacharjee, 2012;Reville, 2014). Yet, several recent studies have failed to replicate this finding (Morton and Harper, 2007;Paap and Greenberg, 2013;Antón et al, 2014), leading many researchers to doubt its validity (de Bruin et al, 2015;Paap et al, 2016), and creating a division in the bilingualism research community between believers and skeptics (Bak, 2016;Bialystok, 2016;Titone et al, 2017). This ambiguous state of the literature is not limited to executive functioning.…”
Section: Introductionmentioning
confidence: 90%
“…Training Test Bialystok, Craik, Klein, and Viswanathan (2004) 8 28 Morton and Harper (2007) 2 28 Martin-Rhee and Bialystok (2008) 8 40 Paap and Greenberg (2013) 20 40 (Poarch & van Hell, 2012) 24 84 7 our study 8 48 Table 4 Number of critical trials in the Simon task: cross-study comparison…”
Section: Studymentioning
confidence: 99%
“…A number of studies controlling for SES indeed found no bilingual advantage (e.g. Morton & Harper, 2007;Paap & Greenberg, 2013;Duñabeitia et al, 2015). However, evidence also exists of a bilingual advantage in socio-economically deprived children (Engel de Abreu et al, 2012;Calvo & Bialystok, 2014).…”
Section: Introductionmentioning
confidence: 99%